Fetal Alcohol Spectrum Disorder and Fine Motor Skills: A Population-based Study of Children in the Fitzroy Valley - Doney, Robyn Michelle (Curtin University, 2017)
Fine motor skills of 108 predominantly Aboriginal children in the remote Fitzroy Valley of Western Australia were evaluated as part of a population-prevalence study on Fetal Alcohol Spectrum Disorder (FASD). Children with FASD were more likely to have poorer handwriting, fine motor skills, and visual-motor integration than children without prenatal alcohol exposure. These novel findings will inform the FASD assessment and diagnostic process and guide therapeutic and service needs.